Ideal body image and socioeconomic factors : exploring the perceptions of Kenyan women - Linette Waltsgott and Adekunle Adedeji and Johanna Buchcik (BMC women's health, 2024)
Background: Non-communicable diseases are an increasing threat in sub-Saharan Africa (SSA), and overweight and obesity are affecting people across all socioeconomic groups. Some studies suggest that big body sizes may be perceived as desirable among women in SSA and that high prevalence of obesity and overweight are especially present in low socioeconomic societies. This study explores the role of socioeconomic factors in the perception of the ideal body among Kenyan women and whether perceptions and beliefs about the ideal body should be considered relevant when targeting the prevention of obesity and overweight. Method: In-depth interviews were conducted with 8 Kenyan women with varying educational backgrounds, aged between 21 and 48, using a qualitative study design. The interviews were conducted in December 2022 and January 2023 in Nairobi, audio-recorded, transcribed and analysed through qualitative content analysis and a coding system using deductive and inductive codes. Results: The participants reported that conclusions about a person’s health and wealth status are drawn based on different body sizes. Furthermore, traditional views about the ideal body size, societal pressure, as well as the women’s own experience with their body size play a role in the perception of an ideal body. Conclusion: Small-sized women desire to gain weight as society may view them as weak and sick. Big-sized women aim to reduce weight primarily due to health complications. Nevertheless, traditionally, a big-sized woman is considered strong and wealthy, creating external pressure on women to fulfil this body image—these findings emphasise traditional aspects in designing culturally sensitive prevention and intervention methods to address overweight and obesity.
Keywords: Ideal Body Image; Kenya; Obesity; Public perception; Socioeconomic status; Tradition